The Effect of Education on Community Attitudes and Actions About Clean and Healthy Living Behavior in Households in the Industrial Area, Morosi Village, Morosi District, Konawe Regency - Papua, Luciana; Azizi Jayadipraja, Erwin; Sunarsih, Sunarsih (Waluya The International Science of Health Journal, 2023)
Introduction: Clean and Healthy Living Behavior in household arrangements, especially in the Konawe district in 2021, amounted to 1,721 households that applied only 36.39% of the 4,729 RTs surveyed. And in 2021 it will increase by 25,721 households that apply by 44.26% from 48,337 RTs surveyed. The results of initial observations made to the community, from 33 Morosi village residents who were interviewed all did not understand what clean and healthy living behavior was. Method: This study uses pre-experimental research methods. The research design used was One-Group Pretest-Posttest. In this research design, group extension methods were used. The research implementation time will be carried out for approximately 30 days starting from April to June 2022. Thus, the total sample for this study is 161 respondents. Result: It is known that the average increase for the attitude variable is 11.83851 with a t-count value greater than t-table (7,315 > 1.61831) and the Action variable with an average increase of 26,27329 and it is known that the t-count for the action variable is greater than t-table (15,611> 1.68299). Conclusion: There is an effect of counseling on increasing community attitudes and actions or practices regarding Clean and Healthy Life Behavior in households in the Morosi Village Industrial area.